Understanding inclusive education: ideals and reality - Haug, Peder (Scandinavian journal of disability research : SJDR, 2017)
The key issue discussed in the article is the main challenges in developing inclusive education. Most European countries have acknowledged inclusive education as a means to secure equal educational rights for all persons. However, the definitions and implementations of inclusive education vary immensely. They are discussed in relation to a narrow and a broad definition of inclusive education, distinguishing between a horizontal and a vertical dimension of the concept. The article also goes into students' learning outcomes in inclusive education as well as teacher competencies for inclusive pedagogy. No country has yet succeeded in constructing a school system that lives up to the ideals and intentions of inclusion, as defined by different international organizations. Placement seems to be the most frequent criterion of inclusive education, to avoid segregation. The quality of teaching and learning processes in inclusive education has lower priority.